2020
DOI: 10.1136/jitc-2020-001367
|View full text |Cite
|
Sign up to set email alerts
|

Combination of gemcitabine and anti-PD-1 antibody enhances the anticancer effect of M1 macrophages and the Th1 response in a murine model of pancreatic cancer liver metastasis

Abstract: BackgroundPancreatic ductular adenocarcinoma (PDAC) is among the most dreadful of malignancies, in part due to the lack of efficacious chemotherapy. Immune checkpoint inhibitors, including anti-programmed cell death 1 (anti-PD-1) antibodies, are novel promising forms of systemic immunotherapy. In the current study, we assessed whether gemcitabine (GEM) combined with anti-PD-1 antibody treatment was efficacious as immunochemotherapy for advanced PDAC using a murine model of liver metastasis.MethodsThe murine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…Moreover, mice administered with this combinatorial therapy demonstrated enhanced intratumoral infiltration of cells of both the innate and adaptive immune system, such as CD11b+F4/80+Ly6C+Ly6G− inflammatory monocytes, CD11b+F4/80highCD206+ M1 macrophages and IFN-γ-expressing CD8a+ and CD4+ T cells with well-known proinflammatory/antitumor properties. In addition, the authors observed a significant upregulation in gene expression of several effector cytokines and chemokines related to anticancer immunity in tumor-infiltrating inflammatory cells [ 38 ]. Another interesting study revealed that in mice inoculated subcutaneously (sc) with LLC cells, administration of both gemcitabine and anti-PD1 resulted in reduced tumor volume and prolonged overall survival of recipients compared to those that received only gemcitabine or anti-PD1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mice administered with this combinatorial therapy demonstrated enhanced intratumoral infiltration of cells of both the innate and adaptive immune system, such as CD11b+F4/80+Ly6C+Ly6G− inflammatory monocytes, CD11b+F4/80highCD206+ M1 macrophages and IFN-γ-expressing CD8a+ and CD4+ T cells with well-known proinflammatory/antitumor properties. In addition, the authors observed a significant upregulation in gene expression of several effector cytokines and chemokines related to anticancer immunity in tumor-infiltrating inflammatory cells [ 38 ]. Another interesting study revealed that in mice inoculated subcutaneously (sc) with LLC cells, administration of both gemcitabine and anti-PD1 resulted in reduced tumor volume and prolonged overall survival of recipients compared to those that received only gemcitabine or anti-PD1.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple clinical trials evaluating CD40 agonists for the treatment of PDAC in combination with chemotherapeutic or targeted agents are ongoing (NCT03214250; NCT04536077; NCT04807972; NCT04888312) and may yield more promising results. Furthermore, the combination of an anti-PD-1 antibody with Gemcitabine showed a beneficial effect in a murine PDAC liver metastasis model, which was explained by an increase of M1-macrophages and a TH1 response [ 182 ].…”
Section: Heterogeneity Of the Stromal Compartment In Pdacmentioning
confidence: 99%
“…However, multiple clinical trials evaluating CD40 agonists for the treatment of PDAC in combination with chemotherapeutic or targeted agents are ongoing (NCT03214250; NCT04536077; NCT04807972; NCT04888312) and may yield more promising results. Furthermore, the combination of an anti-PD-1 antibody with Gemcitabine showed a beneficial effect in a murine PDAC liver metastasis model, which was explained by an increase of M1-macrophages and a TH1 response [182]. Since specific targeting of macrophages spares other immunosuppressive monocytic cell populations which may impair the therapeutic efficacy, targeting of the integrin CD11b/CD18 which highly expressed on several myeloid cell subsets has been suggested as a promising strategy for PDAC treatment.…”
Section: Approaches For Targeted Therapy Of Macrophagesmentioning
confidence: 99%
“…This type of cell death is characterized by a necrolytic release of danger signals that can modify the stroma, change cytokine rates, reduce the presence of suppressive cells such as MDSCs and Tregs, promote the expression of molecules of the major histocompatibility complex (MHC) in cancerous cells and stimulate DC maturation[ 87 ]. In animal models, a synergetic effect has been observed between the combination of gemcitabine and anti-PDL1[ 88 ].…”
Section: Landscape Of Immunotherapy In Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%